Coffee Farmers as Agents of Change in Conservation of Rare Saninten Tree Plants (Castanopsis argantea Blume A.DC) Innovation in Suntenjaya, Lembang, Bandung - Bahtera Segara T (Prospect Publishing, 2023)
Biodiversity development innovations in Indonesia are quite diverse, collaboration between stakeholders is a catalyst for change. Saninten tree (Castanopsis argantea Blume A.DC) is one of the rare plants with endangered IUCN status that is being conserved by PT Pertamina Patra Niaga DPPU Husein Sastranegara in Suntenjaya, Lembang, Bandung. Increasing community capacity in conservation activities is one of the important elements for conservation to be successful. This important element is embodied by inviting coffee farmers around the conservation area to be able to protect rare plants while at the same time planting coffee in the same place, because coffee that grows under the shade of trees will produce coffee beans that have a unique taste.